2019
DOI: 10.1002/1873-3468.13434
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the dopamine receptor‐interacting protein Alix/AIP1 modulates NMDA receptor‐triggered cell death

Abstract: Alix/AIP1 is an adaptor protein involved in apoptosis, endocytic membrane trafficking and brain development. Alix has been found within the human postsynaptic density (PSD) and, since NMDA receptors (NMDARs) are central components of the PSD, we hypothesized that the close proximity of both proteins may allow Alix to influence the downstream pathways following NMDAR activation. NMDARs play important roles in excitotoxicity and we evaluated the effects of recombinant Alix in an NMDAR cell death assay. Overexpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The influx of Ca 2+ through NMDARs is essential for stimulating intracellular signaling cascades to cause cell death, but the precise molecular mechanisms of NMDARs in neuronal death still remain unclear (Hardingham and Bading, 2010 ; Szydlowska and Tymianski, 2010 ). Alix, a known modulator of caspase-dependent and caspase-independent cell death, has been found within the human postsynaptic density (PSD), in which NMDARs are central components and could trigger Ca 2+ -dependent neuronal cell death (Salim et al, 2019 ). Moreover, dopamine signaling is a critically important process in the brain, and dopamine receptors (DARs) are closely related to neurodegenerative diseases such as AD and have become an important target for the prevention and treatment of AD (Reeves et al, 2017 ; Pan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influx of Ca 2+ through NMDARs is essential for stimulating intracellular signaling cascades to cause cell death, but the precise molecular mechanisms of NMDARs in neuronal death still remain unclear (Hardingham and Bading, 2010 ; Szydlowska and Tymianski, 2010 ). Alix, a known modulator of caspase-dependent and caspase-independent cell death, has been found within the human postsynaptic density (PSD), in which NMDARs are central components and could trigger Ca 2+ -dependent neuronal cell death (Salim et al, 2019 ). Moreover, dopamine signaling is a critically important process in the brain, and dopamine receptors (DARs) are closely related to neurodegenerative diseases such as AD and have become an important target for the prevention and treatment of AD (Reeves et al, 2017 ; Pan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that DARs also interact with NMDARs (Lee et al, 2002 ; Liu et al, 2006 ; Devor et al, 2017 ), we speculated that Alix might have the capacity to influence NMDARs triggered neuronal death. Furthermore, it was reported that the close proximity of both Alix and NMDARs allowed Alix to influence the downstream pathways following NMDARs activation in low or absent glutamate/glycine concentrations (Salim et al, 2019 ), and thus, it was speculated that Alix might act as a potential modulator of NMDARs function. Our present study showed that the down-regulation of Alix was significantly attenuated after the treatment with Memantine as an NMDA receptor antagonist in APP/PS1 mice and Aβ 25–35 intracerebroventricular-injected rats, which further confirmed that Alix might remain closely tied to the NMDA-related pathology of AD.…”
Section: Discussionmentioning
confidence: 99%